TI_GERICHTE 12.2020.124 vom 17. Juni 2021 , Appalto - garanzia per difetti - riparazione da parte di un terzo - corresponsabilità - TI Tribunale d'appello (2021)
Appalto - garanzia per difetti - riparazione da parte di un terzo - corresponsabilità